EVALUASI PELAYANAN POSBINDU PENYAKIT TIDAK MENULAR DI WILAYAH KERJA PUSKESMAS JAGASATRU KOTA CIREBON PADA ERA PANDEMI COVID-19 - Ari Nurfikri; Supriadi Supriadi; Badra Al Aufa (Universitas Indonesia, 2020)
This study evaluates the Non-Communicable Disease Posbindu services in the Jagasatru Public Health Center in Cirebon City during the Covid-19 pandemic era seen from the aspects of communication, resources, disposition, and bureaucratic structure. The method used is a qualitative analysis method, with a case study design. The research subjects were eight cadres of Posbindu Non-Communicable Diseases using random sampling technique; data collection was done by in-depth interview technique. This study's results indicate that the evaluation of services from the aspect of communication to the target of the analysis is correct, but has not yet reached the mark of productive age. Evaluation from the aspect of resources can be seen that in the pandemic era, every Non-Communicable Disease Posbindu requires personal protective equipment and health equipment to support services, and there is no cadre regeneration in every Posbindu. Evaluation from the aspect of disposition, the acceptance of cadres as executors is quite good because they perform well in serving participants in limitations. The evaluation of the reporting system's bureaucratic structure has been graded from cadres to health center officers to the Cirebon City Health Office.Keyword: Evaluation, Public Health Center, Posbindu PTM